Three-charged-particle systems in the framework of coupled coordinate-space few-body equations - Sultanov, Renat A.; Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2023)
We study three-charged-particle low-energy elastic collision and particle-exchange reactions with special attention to the systems with Coulomb interaction and an additional nuclear interaction employing a close-coupling expansion scheme to a set of coupled two-component few-body equations. First we apply our formulation to compute low-energy elastic scattering phase shifts for the d+(tμ-)1s collision, which is of significant interest for the muon-catalyzed-fusion D-T cycle. Next, we study the particle-exchange reaction d+(pX-)→p+(dX-) with the long-lived elementary heavy lepton stau X- which can play a critical role in the understanding of the big-bang nucleosynthesis and the nature of dark matter. We also study the total cross sections and rates for two-particle-exchange reactions involving antiprotons (p¯), deuterons (d), and tritons (t), e.g., p¯+(dμ-)1s→(p¯d)1s+μ- and p¯+(tμ-)1s→(p¯t)1s+μ-, where μ- is a muon. The effect of the final state short-range strong (p¯d) and (p¯t) nuclear interactions is significant in these reactions, which increases the reaction rates by a factor of ≈3.